Dynamics of Political Entrepreneurship among the Elites in Post-Colonial Zimbabwe (The Strategic Review for Southern Africa, 2021)
The political arena is now abounding with people who either live ‘off’ or ‘for’ politics. The ferocious competition for people’s votes is akin to economic competition and as this study submits, the politicians are just like business people. Both productive and predatory profit opportunities have pervaded the Zimbabwean political arena where politics is a type of business. Political positions have afforded some people access to economic resources, making politics the quickest way to untold and unending riches. As a result, the political landscape has invited abuse of power thereby decimating not the physical being but the entire moral fibre of the nation. This study shows how Zimbabwean political leaders have turned out to be the primary controllers and distributors of power and resources with the capacity to penetrate society politically and secure their hegemony. Reference is made to politicians belonging to the ruling party Zimbabwe African National Union-Patriotic Front (ZANU-PF) and the opposition Movement for Democratic Change (MDC), where politicians from either party have exhibited, though not uniformly, patterns of misconduct characteristic of political entrepreneurship. This paper applies the theory of the entrepreneur to political behaviour for the purpose of identifying political entrepreneurs and analytically distinguishing them from other government agents.
Keywords: entrepreneurship; resources; politics; vote